BEBERAPA KENDALA DAN UPAYA DALAM PROSES PENAGIHAN TUNGGAKAN PAJAK - Febria Nur Kasimon (Perspektif, 2006)
The role of duty in the increated of state recezption still a moment has so potential. In the development is duty has contribution is very great, which of nation, increation as matter of each obligation. Therefore, obligations that to emerge in tax law is must be fullfill, but its not all obligation fullfill with voluntary by obligationer. The general back pay duty is happen, because obligated taxcareless has fullfill obligation to paying demand tax, foundation letter of remained duty which had publish by office service tax. In the matter of needed law enforcement for trues errection state, receiption, increation, as especially errection law in the process addiction back pay duty, the hope capable and also repair tax director general.